Sequencing of proteins and peptides - Allen, G (Elsevier, 1989)
Although there is a continuing high level of activity in direct studies on protein primary structures, the requirement for partial sequences has provided a major impetus for the development and dissemination of highly sensitive techniques. While retaining the still applicable formidable basis of the original volume, this Revised Edition reflects the shift towards the use of more sophisticated automated high-performance chromatographic techniques.Sequencing of Proteins and Peptides provides you with the most up-to-date information selected to be the most appropriate for laboratory or reference use since, as in the first edition, it is impossible to cover the field of protein sequence determination fully. New information covers: •FABMS •protein recovery methods •Amino acid analysis •Tandem, plasma description, FAB, and Thermospray mass spectrometry. As in the First edition, Appendixes give information on manufacturers and supplies, purification, and safety in the lab.
Laboratory techniques in biochemistry and molecular biology ; Vol. 9
Keywords: klinické laboratorní techniky; molekulární biologie; Clinical Laboratory Techniques; Biochemistry; biologie; chemie, klinická chemie; Molecular Biology; biochemie